Strong reciprocity: norms and preferences governing cooperation and punishment behaviour - Weber, Till O. (2018)
Many problems that societies face have the character of social dilemmas, in which cooperation benefits the whole society but is costly to the individual. The recent literature in experimental economics has focused on uncovering driving factors of cooperative success in social dilemmas. This thesis contributes to this literature and includes three research studies that investigate the influence of individual cooperative dispositions, societal and cultural differences, as well as institutional differences on human cooperative behaviour. Chapter 1 introduces the research questions, discusses the research methods used, and outlines the substantive contributions of the thesis. Chapter 2 presents an experimental test of a common implicit assumption in the literature, which suggests that only people with a cooperative disposition engage in the punishment of defectors in social dilemmas. The experimental test rejects this assumption and shows that individual cooperativeness is independent of one's propensity to punish. Chapter 3 investigates the channels through which culture and societal differences affect cooperative behaviour. The experimental results show that societal differences in behaviour are mainly driven through differences in beliefs about other people's behaviour. Chapter 4 reports on an experimental comparison of informal and formal sanctioning institutions. These experiments show that informal sanctions like peer pressure are necessary to foster high and stable cooperation levels in the long run. Chapter 5 concludes.